ANALISIS KANDUNGAN VITAMIN DAN MINERAL DARI BUAH BERUWAS LAUT(Scaevola taccada) - Pamungkas, Aditya Nindy; Apriandi, Azwin; Suhandana, Made (Marinade, 2019)
The purpose of this study was to determine the content of vitamins, minerals, proximate, and food fibres from Beruwas Laut (Scaevola taccada). This research was conducted descriptively. The results of the research analyzed concluded that the Beruwas Laut (Scaevola taccada) was water content (80.994 %), ash content (0.318 %), lipid content (0.573 %), protein content (0.312 %), and carbohydrate (17.803 %) while the vitamin content in the Beruwas Laut (Scaevola taccada) namely vitamin A (12.415 SI), vitamin B12 (0.025 SI), vitamin E (0.130 SI), vitamin C (22.578 SI) and mineral content in the Beruwas Laut (Scaevola taccada) namely Magnesium (4.326 %), Iron (1.321 %), Calcium (28.775 %), Potassium (116.228 %), Phosphorus (8.519 %), Iodine (13.733 %). Based on the results of the study it can be concluded that the analysis of the content of vitamins and minerals in the Beruwas Laut (Scaevola taccada) contains vitamin C and mineral content of Potassium, the highest research results.